Omphalodes nedimeae (Boraginaceae), a new species from the Mediterranean Region of Turkey - Aykurt, Candan; Sümbül, Hüseyi̇n; Gülben, Mertcan; Sari, Duygu; Konuralp, Leman Yasemi̇n (Phytotaxa, 2021)
A new species of Omphalodes from the high mountain region of Kumluca (Antalya) is described here and named as O. nedimeae. A phylogenetic tree based on the nuclear-encoded ribosomal internal transcribed spacer (ITS) region suggests a close relationship with O. luciliae. The new species differs from the morphological similar species by having dense strigose hairs covering all vegetative parts and dense trichomes on its nutlets. We suggest that it should be in the “critically endangered” threat category according to the International Union for Conservation of Nature (IUCN) criteria.